1966
DOI: 10.1021/j100881a032
|View full text |Cite
|
Sign up to set email alerts
|

Micellar Properties and Critical Opalescence of Dimethyalkylphosphine Oxide Solutions

Abstract: Phase diagrams and light-scattering measurements of a homologous series of dimethylalkylphosphine oxides are used to determine the micellar molecular weights and their relation to consolute phase boundaries in these systems. The temperature dependence of micellar molecular weights is discussed with regard to both light-scattering and solution theory, and it is concluded that, in systems which show consolute boundaries, the lightscattering behavior can be qualitatively explained on the basis of existing theory … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
39
1

Year Published

1967
1967
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 101 publications
(42 citation statements)
references
References 3 publications
2
39
1
Order By: Relevance
“…One of the early light scattering examinations of dodecylhexaoxyethylene glycol monoether (C12E6) suggested the formation of micelles of micellar weight in the region 60,000-84,600 at ambient temperatures and indicated that there was a variation with temperature; it was also clear that under these conditions the micelles were non-spherical [1]. Subsequent light scattering studies on C12E6 and other homogeneous polyoxyethylene glycol monoethers reported a pronounced variation of micellar weight with temperature [2,3] and similar results were obtained with alkyldimethyl phosphine oxides [4] and alkylsulphinyl alkanols [5]. These authors concluded that interpretation of the light scattering results was complicated by the non-ideality of the system.…”
mentioning
confidence: 64%
“…One of the early light scattering examinations of dodecylhexaoxyethylene glycol monoether (C12E6) suggested the formation of micelles of micellar weight in the region 60,000-84,600 at ambient temperatures and indicated that there was a variation with temperature; it was also clear that under these conditions the micelles were non-spherical [1]. Subsequent light scattering studies on C12E6 and other homogeneous polyoxyethylene glycol monoethers reported a pronounced variation of micellar weight with temperature [2,3] and similar results were obtained with alkyldimethyl phosphine oxides [4] and alkylsulphinyl alkanols [5]. These authors concluded that interpretation of the light scattering results was complicated by the non-ideality of the system.…”
mentioning
confidence: 64%
“…8. Again, it is the less polar head group of C 12 DEPO which is responsible for its lower water solubility, which influences both the cmc [21] a Note that the coordinates of the lower critical consolution point are not given in [2] but were estimated from the respective miscibility gaps. Due to the low number of data provided in [2] the c c could not or only approximately be determined and the miscibility gap.…”
Section: Miscibility Gapsmentioning
confidence: 99%
“…For example, extensive surface tension [7][8][9][10][11][12][13] and surface rheology [14][15][16][17][18][19][20] studies have been carried out with a focus on the properties of C 12 DMPO. In addition, the binary water-surfactant phase diagrams of C 8 DMPO [21], C 10 DMPO [21], C 12 DMPO [2,3,21], and C 14 DMPO [2,3] were studied, and the formation of microemulsions with C 10 , C 12 , and C 14 DMPO was investigated [3]. Finally, there are studies on the interactions between C 12 DMPO surfactant layers adsorbed on hydrophobized mica [22] and on the adsorption of C 10 DMPO and C 12 DMPO on silica [23,24].…”
Section: Introductionmentioning
confidence: 99%
“…The aqueous phase diagrams for several members of the APO family of compounds have been determined over a broad concentration range [13]. The lower consulate temperature (LCT) for 10% solutions of APO10 and APO12 was approximately 125 and 40 • C, respectively.…”
Section: Introductionmentioning
confidence: 99%
“…The phase separation temperature was modeled using regular solution theory, and it is related to the molecular weight of the micelles and mixed micelles [15]. The composition of the two liquid phases that result from heating aqueous solutions of several aqueous APO and APO/PL mixtures above the lower critical solution temperature (LCST), or cloud point, has been determined [13,16], and it is possible that the liquid-liquid phases that are formed by these mixtures have potential use for protein separations, particularly membrane proteins which require non-conventional methods [17].…”
Section: Introductionmentioning
confidence: 99%